2013
DOI: 10.1111/jog.12274
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences in psychiatric symptoms and eating attitudes between pregnant women with hyperemesis gravidarum and healthy pregnant women?

Abstract: We suggest that HG appears to be associated with depression and anxiety symptoms rather than deterioration of eating attitudes and body image. However, these results should be confirmed by prospective and clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
(30 reference statements)
1
29
1
1
Order By: Relevance
“…Therefore, it was concluded that the eating attitudes of the HG group were more pathological than those of the control group. This finding is in conflict with the study of Annagur et al (26) suggesting a lack of difference between ED and non-ED pregnant cases in terms of eating attitudes. Albeit, an association of HG with pathological eating attitudes was found in our study, studies based on ED diagnosis through structured psychiatric interviews are needed to establish the relationship between HD and ED.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Therefore, it was concluded that the eating attitudes of the HG group were more pathological than those of the control group. This finding is in conflict with the study of Annagur et al (26) suggesting a lack of difference between ED and non-ED pregnant cases in terms of eating attitudes. Albeit, an association of HG with pathological eating attitudes was found in our study, studies based on ED diagnosis through structured psychiatric interviews are needed to establish the relationship between HD and ED.…”
Section: Discussioncontrasting
confidence: 94%
“…It was reported in numerous studies that the severity of depression and anxiety could be more in pregnant cases with HG than it is in the healthy pregnant cases (7). In studies conducted in our country as well, a significant association of HG with depression and anxiety was found (5,(23)(24)(25)(26). In the study by Uguz et al (3), the prevalence of mood disorders such as major depression and anxiety disorders was detected to be higher in pregnant cases with HG than it is in healthy control group.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Şimşek et al [21] demonstrated that women complicated with serious vomiting during their pregnancies had noticeably more anxiety and depression than a wellmatched control group of healthy antenatal women. In an elegant article by Annagür and colleagues [22], it was reported that depression and anxiety scores were significantly higher in women with HG and HG appears to be associated with depression and anxiety symptoms rather than deterioration of eating attitudes and body image. In this context, no difference was noted in the present study between NVP grades and sociodemographic factors, including pregnancy characteristics, gestational age, patient age, educational status, smoking, and employment status.…”
Section: Discussionmentioning
confidence: 98%
“…Senturk et al, reported that patients who suffered from HG experienced more frequent postpartum depression, negative psychiatric status, and higher probability of depression in the postpartum period (34). Annagur et al, concluded that HG seems to be associated with depression and anxiety symptoms (35). In a systematic review and meta-analysis, it was noted that frequency of depression and anxiety was significantly higher in patients with HG (6).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%